An Endodontic Enigma: A Case Report of External Inflammatory Root Resorption-2 years Follow up (City Dental College Journal, 2018)
In dentistry,root resorption is the breakdown or destruction and subsequent loss of the root structure of a tooth caused by living body cells attacking part of the tooth. When the damage extends to the whole tooth is called tooth resorption. Severe root resorption is very difficult to treat and often requires the extraction of teeth. Root canal therapy has been shown to be a verysuccessful means of treating inflammatory resorption. It has been recommended to include a calcium hydroxide paste in the root canal therapy to enhance the success of the treatment out come. Calcitonin has also been suggested as an interim root canal medicament to assist in the inhibition of osteoclastic bone and dentin resorption. Calcitonin penetrates the dentinal tubules in the out word direction, thus exerting a direct effect DOI: http://dx.doi.org/10.3329/cdcj.v10i1.13833 City Dent. Coll. J Volume-10, Number-1, January-2013